Renewable Energy, Climate Change and Sustainable Development Nexus in an Era of Globalisation. The Role of Global Governance - Taran, Alexandra-Madalina; Ginguta , Andrea; Nachescu, Miruna-Lucia; Pirtea, Marilen-Gabriel; Tarczynska-Luniewska, Malgorzata; Noja, Gratiela-Georgiana (Transformations In Business & Economics, 2025)
Globalisation, facilitated by foreign direct investment, is leading to an increase in energy consumption, particularly of non-renewable sources, resulting in detrimental environmental effects. Globalisation promotes the use of renewable energy sources, and carbon emissions start to decline, sustaining economic and social development. This study sets out to assess the influence of global governance on environmental sustainability and its implications upon economic and social development in the era of globalisation. In this respect, advanced methodological approaches are applied, namely the structural equation model (SEM), to model longitudinal data collected from the period between 2002 and 2021 within 27 Member States of the European Union. The results highlight that the EU-27 countries must prioritise the globalisation process, as it has the potential to reduce CO2 emissions, with the EU-27 countries being in need for tailored policies and strategies that can effectively combat environmental degradation by exchanging and implementing environmentally friendly technologies.
Keywords: renewable energy; sustainable development; globalisation; global governance